2002
DOI: 10.1029/2001ja009025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar wind variations on the midlatitude ionosphere

Abstract: [1] It is known that the solar wind has significant effect on the magnetospheric convection and that magnetospheric electric fields can penetrate into the midlatitude and low-latitude ionosphere. In this paper, we present observations of midlatitude ionospheric plasma perturbations during two events. In one event, the interplanetary magnetic field (IMF) oscillated between southward and northward with a period of $2 hours, while the solar wind pressure was relatively stable. In the other event the solar wind dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…This periodicity may be related to the variations of the same period in solar-wind density around the WHI. Huang, Foster, and Erickson (2002) showed that changes in solar-wind dynamical pressure can cause changes in electric fields and thus variations of global F2 peak electron densities. It is also possible that the periodicity was the results of the nonlinear interaction of the variations of different periods, such as the 9-day and 13.5-day variations.…”
Section: Discussionmentioning
confidence: 99%
“…This periodicity may be related to the variations of the same period in solar-wind density around the WHI. Huang, Foster, and Erickson (2002) showed that changes in solar-wind dynamical pressure can cause changes in electric fields and thus variations of global F2 peak electron densities. It is also possible that the periodicity was the results of the nonlinear interaction of the variations of different periods, such as the 9-day and 13.5-day variations.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies suggested that the ionospheric electron content perturbations were also caused by the penetration of magnetospheric electric fields, which were controlled or modulated by the oscillations in the IMF/solar wind pressure (Borovsky, et al, 1993;Fejer and Scherliess, 1998;Sobral et al, 1997;Huang et al, 2002;Unnikrishnan, et al, 2005). The energy and particle injection that takes place during magnetospheric disturbances produce multiple changes to the Earth's high latitude ionosphere-thermosphere system (Pincheira et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…When the magnetosphere is compressed by an enhancement of the solar wind pressure, the dayside magnetopause current is intensified, resulting in an increase of the low-latitude geomagnetic field. IMF reorientations influence the low-latitude geomagnetic field through an electric field penetration process [Nishida, 1968;Fejer et al, 1979;Kelley et al, 1979Kelley et al, , 2003Kikuchi and Araki, 1979;Huang and Foster, 2001;Huang et al, 2002Huang et al, , 2004Huang et al, , 2005Huang et al, , 2006. When the IMF turns from northward to southward, the interplanetary electric field can penetrate into the equatorial ionosphere and cause an eastward electric field in the dayside ionosphere, resulting in disturbances in the ionospheric currents and magnetic field.…”
Section: Introductionmentioning
confidence: 99%